Partnering for rotavirus vaccine introduction in India: A retrospective analysis. Issue 44 (22nd October 2021) - Koshal, SS.; Ray, A.; Mehra, R.; Kaur, A.; Quadri, SF.; Agarwal, P.; Kapur, S.; Debroy, A.; Haldar, P.
Highlights: Rotavirus vaccine (RVV) introduction in India highlights the successful role of public–private partnership (PPP) in the development and pan India delivery of a new vaccine in the country in a short span of time. The combined and synergistic strengths of all the partners led to a successful and efficient implementation of RVV introduction. The study highlights how pre-existing health service systems can be adapted with newer approaches for enhanced coordination, management and nurturing the partners' landscape. PPP can be successfully used and replicated for introducing other new vaccines, strengthening the health systems, or improving other emerging public health priorities such as pandemics. Abstract: Background: The pre-existing partner network created in India for the delivery of polio vaccines was initially used to eradicate polio and later on embedded in the health systems network to promote routine immunization and other health interventions efficiently. The experience from this network offered lessons for strengthening the health care systems and provided a well-established network that could be utilized for other vaccine initiatives. It has also been established that successful partnerships between a broad range of stakeholders provide support, strengthen the health system, and accelerate vaccine innovation, introduction, access, logistics, and communication support. However, beyond polio eradication, there have not been too many documented success stories of vaccine introduction, which could be replicated in other new vaccine introductions and allied health initiatives. The authors have reviewed the successful and time-bound introduction of rotavirus vaccine (RVV) in India in the present article. Methods: The review was conducted based on a partnership framework which analysed multiple factors-partnership prerequisites, partnership model, partnership process, and partnership performance, thereby providing a comprehensive insight into the successful utilization of partnership networks for rotavirus vaccine introduction under the Universal Immunization Program in India. Results & conclusion: The review also highlights the role of a lead agency in creating a fertile ground for lush, efficient, and effective partnerships amongst different stakeholders. The already existing RVV partnership framework reviewed by the authors can be successfully utilized for future new vaccine introductions.